ANALISIS PERUBAHAN MAKNA MELUAS PADA KOMENTAR NETIZEN PADA AKUN INSTAGRAM FIERSA BESARI - Robiatul Adawiyah; Rita Arianti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to examine and analyze the changes in the expanded meaning of netizens' comments on Fiersa Besari's Instagram account (@fiersabesari). This research method uses a qualitative descriptive method. The results of the study indicate that the expansion of expanded mea ning occurs in netizens' comments on the Indonesian artist's Instagram social media account. This expansion of meaning most likely occurs as a result of increasingly rapid technological and modern developments. Netizens as language users are also influenced by the conditions that occur around them. In addition, changes in expanded meaning also show that language is static and not dynamic. There are several characteristics that language has, namely language can live and continue to develop if the language is continuously used by its users and language can change its meaning according to the wishes of its users. In other words, there are no boundaries in language, which means language is able to develop and change according to the needs of its users. This phenomenon of changing meaning is also a concrete example that language does experience development and language is arbitrary.